Text Cryptography Based on Three Different Keys (مجلة المنصور, 2023)
Secure information transmission over the internet is becoming an important requirement in data communication. These days, authenticity, secrecy, and confidentiality are the most important concerns in securing data communication. For that reason, information hiding methods are used, such as Cryptography, Steganography and Watermarking methods, to secure data transmission, where cryptography method is used to encrypt the information in an unreadable form. At the same time, steganography covers the information within images, audio or video. Finally, watermarking is used to protect information from intruders. This paper proposed a new cryptography method by using three different keys to make the system harder to break by outsider attackers (where the 1st and 3rd encryptions keys are numerical keys, while the 2nd key is string). This system is done based on seven steps; the first step is converting the plaintext based on the first generated key that leads to substitute each character in plaintext, the second step is embedding second generated key with the message that want to send, the third step is done by converting text to their equivalent ASCII format. The fourth step is converting these ASCII format to Binary numbers; then, these numbers are shifted based on the third generated key. These binary numbers are converted to ASCII, and the last step is to convert ASCII to their equivalent characters. The achieved text is the ciphertext that will be sent.